Cancer Treatment; New Strategies/New Hopes - Ebrahim Salehifar; Maria Tavakkoli-Ardakani (Research Center for Rational Use of Drugs (RCRUD), 2020)
Beginning in the early 2000s and based on the better understanding of the biology of cancer, new drugs have been developed that target specific molecular pathway in malignant cells. There has been a significant shift from the development of classic cytotoxic agents toward targeted therapies. Dose limiting toxicities of target therapies are often different. These agents have unique mechanism of action and are very specific for one or several key cellular biologic pathways. Introduction of these agents was associated with a significant progress in the management of some cancers. A good example is use of tyrosine kinase inhibitor (TKIs) for the treatment of chronic myeloid leukemia. Imatinib was the first one and several other TKIs such as dasatinib, nilotinib, bosutinib and ponatinib have been developed.